The six secrets of change : what the best leaders do to help their organizations survive and thrive - Fullan, Michael (San Francisco : Jossey-Bass, 2008)
In this book Fullan explores essential lessons for business and public sector leaders for surviving and thriving in today's complex environment. He draws on his acclaimed work in bringing about large-scale and substantial change in education reform in both public school systems and universities, as well as engaging in major change initiatives internationally. The Six Secrets of Change is filled with lessons that are insightful, actionable, and concisely communicable. These lessons are'secrets' not because there is a conspiracy to hide them from public view, but because they are often difficult to grasp in their deep meaning, and challenging to appreciate and act on in combination. Fullan makes these so-called secrets accessible and useful and offers illustrative examples from a variety of businesses, health organizations, and public education systems.
Includes bibliographical references (p. 137-143) and index.
Keywords: Organizational change; Communication in organizations; Interpersonal communication; Employee empowerment; Employee motivation